1999
DOI: 10.1180/000985599546181
|View full text |Cite
|
Sign up to set email alerts
|

Cottonseed oil bleaching by acid-activated montmorillonite

Abstract: A progressive decrease in cation exchange capcity (CEC) values was observed by treating Ca-montmorillonite with sulphuric acid solutions and this can be understood in terms of the layered structure of the clay. Elemental analysis showed that moderate activation occurred and only 25–30% of the octahedral cations were removed. At the same time the total surface area and the clay acidity increase. X-ray and FTIR data confirmed that acid activation affects both the octahedral and the tetrahedral sheets. The effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(37 citation statements)
references
References 32 publications
(33 reference statements)
4
24
0
2
Order By: Relevance
“…The occurrence of silicates and aluminosilicates in both samples is confirmed by other peaks in the FTIR spectra, such as the one at 692 cm −1 , which we associate with Si-O bending, and the peaks at 878 and 911 cm −1 in the fossil spectrum, which we associate with Al-OH stretching [16]. Stretching vibrations of Si-O-Si [15][16][17] were observed at 1,024 and 1,032 cm −1 in the IR spectra of the fossil and matrix, respectively, while a band at 1,120 cm 1 is associated to a bending of the Si-O unit [15]. Finally, the IR spectra of both the fossil and the matrix show vibrations between 3,600 and 3,735 cm −1 , which we associate with Si-OH stretching.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…The occurrence of silicates and aluminosilicates in both samples is confirmed by other peaks in the FTIR spectra, such as the one at 692 cm −1 , which we associate with Si-O bending, and the peaks at 878 and 911 cm −1 in the fossil spectrum, which we associate with Al-OH stretching [16]. Stretching vibrations of Si-O-Si [15][16][17] were observed at 1,024 and 1,032 cm −1 in the IR spectra of the fossil and matrix, respectively, while a band at 1,120 cm 1 is associated to a bending of the Si-O unit [15]. Finally, the IR spectra of both the fossil and the matrix show vibrations between 3,600 and 3,735 cm −1 , which we associate with Si-OH stretching.…”
Section: Resultssupporting
confidence: 51%
“…This indicates that the fossil and matrix contain other minerals. The peak at 526 cm −1 is assigned to Al-Si-O bending [15][16][17], possibly due to aluminosilicate crystalline structures. The occurrence of silicates and aluminosilicates in both samples is confirmed by other peaks in the FTIR spectra, such as the one at 692 cm −1 , which we associate with Si-O bending, and the peaks at 878 and 911 cm −1 in the fossil spectrum, which we associate with Al-OH stretching [16].…”
Section: Resultsmentioning
confidence: 98%
“…There are discrepancies about the respective influence of the SiO 2 and Al 2 O 3 contents of adsorbents and their efficiency (14,15,18,19). Acid activation of clay generally leads to an improvement of bleaching capacity (17,18,21). However, few authors (17)(18)(19)(20) characterized the texture of the adsorbents; Zaki et al (18) found that the bleaching capacity of activated natural clays varied with pore size and an optimum was observed at a pore diameter of 10 to 12 nm.…”
Section: Introductionmentioning
confidence: 93%
“…A number of studies have been carried out on the removal of pigments from cottonseed oil by adsorption (12)(13)(14)(15)(16)(17)(18)(19)(20)(21). The results obtained are hardly comparable since the experimental conditions are different from each other and the examined systems are often complex.…”
Section: Introductionmentioning
confidence: 96%
“…This result clearly indicates that clay can remove peroxides concomitantly as well as color impurities from a crude fatty acid solution. The destruction of peroxides in oils by acid-activated clays has been demonstrated in previous reports [17,18,26,27].…”
Section: Removal Of Peroxides During Decolorizationmentioning
confidence: 73%